Imperative Sentences in Java Ngoko in North Sumatra - Nanda Dwi Astri; Oktaviandi Bertua Pardede (RIRAI Publisher, 2021)
This study uses a qualitative method. Qualitative method is a method that uses descriptive methods to describe data by describing related events both in writing and verbally. The research procedure consists of three stages, namely the stage of data collection, data analysis, and presentation of data analysis. The method used in data collection is the method of observing. The technique used in data collection is a free-to-conversation listening technique by observing and recording data in the form of imperative sentences in the Ngoko Javanese language in North Sumatra. The purpose of this study is to increase knowledge and increase understanding of language command sentences Java Ngoko in North Sumatra. The source of the data in this research is the people in Bandar Tengah village, Bandar Khalipa h, North Sumatra as speakers of the Javanese Ngoko language. Based on the results of the study, imperative sentences in Javanese. Ngoko contain the intent to command, prohibit, invite, order repeatedly, invite, request, be angry, and ask for help.